Penerapan Teknik Penerjemahan dalam Peningkatan Kompetensi Penerjemah PT Indo Lingua Translocalize - Ina Sukaesih; Farizka Humolungo; Septina Indrayani; Fanny Puji Rakhmi; Taufik Eryadi Abdillah (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2026)
This community service program aimed to implement research findings on Molina and Albir’s (2002) translation techniques among translators at PT Indo Lingua Translocalize. The partner is a language service company established in 2009, specializing in Indonesian translation, offering services such as translation, interpreting, and complementary services, including subtitling, desktop publishing (DTP), voice-over, copy-editing, reviewing, linguistic validation, and CAT tools (SDL Trados) distribution. The program was initiated in response to the partner’s need to enhance the quality of literary translation, particularly in terms of accuracy, acceptability, and readability of cultural elements. The program was conducted through theoretical input, interactive discussions, translation practice, and evaluation using pre-tests and post-tests. The method employed was Participatory Action Research (PAR) with a participatory empowerment approach. The findings indicate improved participants’ understanding of translation techniques and their ability to appropriately apply these techniques to literary texts. Participants also reported positive responses regarding the relevance of the materials, clarity of delivery, and professional benefits. This program contributes to strengthening translators’ competence and supports the preservation of local languages through research-based translation practices.